Salts and cocrystal of etodolac: advantage of solubility, dissolution, and permeability - Rai, Sunil K.; Allu, Suryanarayana; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
{Etodolac (ETD) is a nonsteroidal anti-inflammatory drug (NSAID) approved by the United States Food and Drug Administration (US-FDA) in 1991 for the treatment of rheumatoid arthritis. Because of its poor aqueous solubility and high permeability, ETD falls under Biopharmaceutics Classification System (BCS) Class II drug. The present study was aimed to screen stable salts and cocrystals of ETD using Generally Recognized as Safe (GRAS) and a few non-GRAS coformers. Crystallization of five salts (i.e.

Salts, solvates and hydrates of the multi-kinase inhibitor drug pazopanib with hydroxybenzoic acids - Rai, Sunil K.; Baidya, Debjani; Nangia, Ashwini K. (Crystengcomm, 2021)
The marketed formulation of pazopanib (PAZ) suffers from low and variable bioavailability because of its poor dissolution rate and photostability issues. The drug falls under Biopharmaceutics Classification System (BCS) class II of low solubility and good permeability. The hydrogen bonds and supramolecular interactions in crystalline forms of PAZ with hydroxybenzoic acids (HBAs) and dihydroxybenzoic acids (DHBAs), as well as its salts are analyzed. Ten X-ray crystal structures of PAZ which include the reference drug, a tetrahydrofuran solvate (PAZ center dot THF) and eight salts with HBAs/DHBAs are reported. There is proton transfer from the carboxylic group of the coformer acid to the most basic nitrogen atom of the 2-aminopyrimidine ring of PAZ in all cases. Two salts were crystallized in neat form, while the remaining six are solvates and hydrates. The crystal structure of PAZ is stabilized by sulfonamide and 2-aminopyrimidine homosynthons of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in an R2(2)(8) ring motif. PAZ center dot HBA/DHBA salts consistently contain the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- synthon of the R2(2)(8) ring. The sulfonamide homosynthon of PAZ is disrupted in preference to the formation of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in salt structures. The presence of an additional basic nitrogen atom in the indazole ring of PAZ promotes hydration and solvation through the O-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bond. Whereas the formation of salts is desirable for pharmaceutical formulation, the inclusion of adventitious solvent and/or water molecules with hydroxybenzoic acid coformers in the cocrystal-salt products is a limitation for this class of coformers. The stability problem faced with hydrates and solvates of PAZ center dot HBA/DHBA salts means that their formation must be carried out by strictly anhydrous procedures. The consistent occurrence of the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- ring synthon is discussed in relation to the previous results of Aakeroy, Nangia and Zaworotko groups on similar acid-base multi-component systems.

Synthesis of ternary cocrystals, salts, and hydrates of acefylline with enhanced dissolution and high permeability - Allu, Suryanarayana; Garai, Abhijit; Chernyshev, Vladimir V.; Nangia, Ashwini K. (Crystal Growth & Design, 2022)
Acefylline (ACF) is a stimulant xanthine derivative drug, which is formulated as a piperazine salt for the treatment of bronchial asthma. ACF falls under BCS class IV category of low solubility and poor permeability, which together limit the bioavailability and efficacy of the drug. In this work, ACF binary and ternary cocrystals, salts–cocrystals, and their polymorphs are synthesized by cocrystallization with several coformers. Two different methods were adopted for the supramolecular assembly of the ternary systems A.B.C: (1) first, binary adducts A.B or A.C were crystallized by grinding a slurry of the components in a suitable solvent and then C was added and grinding was continued; and (2) all three components were taken in a solvent slurry and ground together. The former method was found to be superior in affording the ternary salt/cocrystal. The role of laboratory seeding is implicated to explain the variation in crystallization results at different stages of the project. Crystal structures of the product’s binary and ternary systems were solved by single-crystal X-ray diffraction and powder X-ray diffraction data for structure solution. The crystal structures show the recurrence of carboxylate–pyridinium and imidazole–acid heterosynthons in the binary and ternary adducts. The intermolecular interactions between ACF and the coformer are analyzed by Hirshfeld surfaces, 2D fingerprint plots, and an energy framework. The permeability of ACF increases in binary and ternary systems with selected coformers. The fast dissolution and high permeability of ACF-PIP make this salt an improved crystalline formulation of acefylline.